Penerapan Teknik Panning untuk Menciptakan Ketegangan dari Segi Visual pada Film Tarung Sarung - Darwatan Derajat; Dani Manesah (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2025)
This study analyzes the role of the panning technique in creating visual tension in the film “Tarung Sarung” (2020), an Indonesian action-adventure film that blends action with the local culture of Makassar. The panning technique, which involves the horizontal movement of the camera to follow the subject or expand the space, is used strategically in key scenes such as fight sequences, chases, and character interactions to enhance the dynamics and intensity of the story. A qualitative approach with descriptive analysis methods was used to explore how this technique influences the audience's perception and supports the film's narrative. The analysis reveals that panning not only clarifies movement in action scenes but also adds emotional depth and showcases the beauty of Indonesian culture and landscapes. This technique is effective in creating tension and directing the audience's attention to important elements of the story. This study is expected to contribute to a deeper understanding of the use of cinematographic techniques in enriching the movie-watching experience, particularly in action and locally rooted genres.